Tne folk plays and spectacles of Anatolia turkish. (Eurasian Journal of Philology Science and Education, 2015)
Anatolia Turkish folk play and spectacles assume importance with its the entertaining and training towardswhich are irreplaceable and valuable examples of the people thinking and courage of humour, imitation, song, dance,word and word play.The Anatolia Turkish folk play and spectacles which have ancient history have spread under the name of"Seyirlik köy oyunları", "Kukla", "Meddahlık", "Karagöz" and "Ortaoyunu" widely. By describing of playing rules ofthis play and spectacles, it is given brief information about their similarity and different peculiarities, the generalfeatures, the origin and what meaning attainted in the article.
Keywords: Village plays; Doll; Laudation; Black-eyed; Middle play